A single-chain immunotoxin against carcinoembryonic antigen that suppresses growth of colorectal carcinoma cells. - Akamatsu, Y; Murphy, J; Nolan, K; Thomas, P; Kreitman, R; Leung, S; Junghans, R (1998)
We have engineered an anti-carcinoembryonic antigen (CEA) single-chain immunotoxin derived from humanized anti-CEA antibody (hMN14) and a truncated Pseudomonas exotoxin (PE), PE40. The purified anti-CEA immunotoxin (hMN14(Fv)-PE40) was first measured for binding affinity against a CEA-positive colorectal carcinoma cell line and compared with its parental IgG and the monovalent Fab fragment. The Ka of sFv-PE40, Fab, and IgG were 5 x 10(7), 6 x 10(7), and 3 x 10(8) M(-1), respectively. There was no significant affinity loss by conversion of Fab to the single-chain Fv, but these monovalent forms were 5-6-fold reduced in affinity compared with the parental IgG. In cytotoxicity assays, the hMN14(Fv)-PE40 showed specific growth suppression of CEA-expressing colon cancer cell lines MIP-CEA (high CEA) and LS174T (moderate CEA) with IC50s of 12 ng/ml (0.2 nM) and 69 ng/ml (1.1 nM). These IC50s correlated inversely with the surface expression of CEA, such that 50% killing was equivalent for each cell type when expressed in toxin molecules bound/cell (3000-5000). The presence of soluble CEA up to 1000 ng/ml did not affect the cytotoxicity against CEA-expressing cells, with 50% suppression only at 4000 ng/ml that correlated with the binding Kd of the single-chain Fv. The stability of the hMN14(Fv)-PE40 molecule at 37 degrees C was confirmed by bioassay and by lack of aggregation. Our hMN14(Fv)-PE40 may be clinically useful for tumors with high CEA expression without affecting normal tissues with low or absent CEA, even in patients with high soluble antigen levels.